2020
DOI: 10.1177/1479973120940677
|View full text |Cite
|
Sign up to set email alerts
|

Serum cystatin C: A potential predictor for hospital-acquired acute kidney injury in patients with acute exacerbation of COPD

Abstract: Hospital-acquired acute kidney injury (HA-AKI) is associated with poor prognosis. In this study, we evaluated whether serum cystatin C on admission could predict AKI in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). The retrospective study was conducted using data on adult inpatients with AECOPD from January 2014 to January 2017. A total of 1035 patients were included, among which 79 (7.6%) with HA-AKI were identified. Univariate and multivariate logistic regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…17 Chen et al indicated that hospital-acquired AKI was 7.9% in AECOPD patient. 18 Another study reported a higher AKI occurrence in AECOPD patients, Wan et al illustrated that 1768 patients admitted to Nanjing First Hospital with a principal diagnosis of AECOPD. Of these, 377 (21%) patients had AKI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Chen et al indicated that hospital-acquired AKI was 7.9% in AECOPD patient. 18 Another study reported a higher AKI occurrence in AECOPD patients, Wan et al illustrated that 1768 patients admitted to Nanjing First Hospital with a principal diagnosis of AECOPD. Of these, 377 (21%) patients had AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that AECOPD patients complicated with AKI were more likely to require non-invasive mechanical ventilation, had a longer duration of mechanical ventilation and duration of hospital stay, higher in-hospital mortality and higher allcause readmission than those without AKI. [16][17][18][19] Hence, it is important to seek biomarkers or risk model for early detection, early diagnosis, and early intervention of the disease can significantly improve prognosis and reduce patient mortality. Chen et al evaluated whether serum cystatin C on admission could predict AKI in patients with AECOPD and the results demonstrated that serum cystatin C has the potential for use to predict the risk of HA-AKI in patients with AECOPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation